STUDI KOMPARASI PEMAHAMAN KONSEP SISTEM PERNAPASAN MANUSIA MELALUI PENERAPAN PEMBELAJARAN KONSTRUKTIVISME TIPE NOVICK DIPADU CONCEPT MAP DAN CERAMAH BERVARIASI - METI INDROWATI, ROILA DEWI MASRUROH (Prodi Pendidikan Biologi FKIP UNS, 2014)
This research is aim to find out the different comprehension of human respiration system concept in the Novick type of constructivism learning with concept map and the varied lecturing learning. This study was a quasi-experimental research using Post-test Only With Nonequivalent Groups research design. The sampling technique used was Cluster Sampling one. The populations of this research were all of 11th degree students of science at SMA Negeri 2 Karanganyar in academic year 2012/2013. The samples of this research were the students of 11th Imersi I as experiment group and 11th Imersi II as control group. Technique of collecting data used was a multiple choice test with reasoning, essay test, and observation sheet. The hypothesis testing was carried out using t-test. The conclusion of research that there isn?t different comprehension of human respiratory system concept between the Novick type of constructivism learning with concept map and the varied lecturing learning. Keywords: Concept map, Novick Type of Constructivism Learning, the Varied Lecturing, Comprehension of Human Respiration System Concept